THE EFFECTIVENESS OF PROJECT BASED LEARNING MODELS ON STUDENTS' ECOLITERACY ABILITIES IN SOCIAL STUDIES LEARNING - Nanda Lintang Elfrida; Tetep; Eldi Mulyana (Journal Civics And Social Studies, 2023)
At the end of the 20th century, the world community was faced with a series of global issues including poverty, health and the environment. The main and dominant issue is environmental problems. The environment is one of the most important things because it provides all the needs of human life as well as the learning environment. Even though students realize the importance of a clean learning environment, the opposite condition occurs in the school environment. In a factual context, students' attitudes towards the environment have not been fully formed. Therefore it is necessary to understand the importance of environmental cleanliness for students through ecoliteracy activities. This study aims to determine the effect of the Project Based Learning model in social studies learning on increasing the ecoliteracy of students in junior high schools. This research was conducted at Asy-syarifiyah Middle School. The research subjects consisted of two classes, namely class VII A as the control class and class VII B as the experimental class. The results of the study show that there is an increase in ecoliteracy from the cognitive, affective and psychomotor aspects. This is evidenced by the value of Sig. (2-tailed) is 0.000 <0.05 then H0 is rejected and Ha is accepted. So it can be concluded that there is an average difference between the learning outcomes of the Pre-test and Post-test, which means that the Project Based Learning learning model increases Ecoliteracy.